FRI0206 Plasma homocysteine levels in patients with systemic sclerosis. (1st June 2001) - Pirildar, T; Turgan, N; Tunc, E; Turk, T; Ozmen, D; Keser, G; Bayindir, O; Doganavsargil, E
Abstract : Background: Objectives: Homocysteine is a nonessential amino acid containing sulfur. Homocysteine has a toxic effect on the endothelium suggesting that it may take part in the etiopathogenesis of the diseases with vascular impairment. Since complex etiopathogenesis of systemic sclerosis (SSc) involves endothelial injury and activation, elevated plasma homocysteine levels might be expected in this disease. Standing from this point, we investigated plasma homocysteine levels in patients with limited (ISSc) and diffuse (dSSc) systemic sclerosis and in healthy controls. Methods: Serum samples were collected from 59 (31 limited and 28 diffuse; F/M:56/3 male) patients with systemic sclerosis attending Ege University Rheumatology department, and 27 age and sex matched healthy controls were included in the study. Homocyteine was measured by high-performance liquid chromotography. Hyperhomocyteinemia may occur due to diabetes mellitus, hyperlipidemia and vitamin B12, folic acid deficiencies. Therefore, patients with these conditions excluded from the study. Results: Statistical analysis was performed using one way analysis of varience test. All data are presented as mean = SD. A p value <0.05 was accepted as statistically significant. Plasma homocyteine levels in patients with diffuse SSc (16.31 ± 5.916 mmol/L) and limited SSc (13.27 ± 8.352 mmol/L) were significantly higher than healthy controls (6.34 ± 1.540 mmol/L). When we compared the two subgroups of SSc, plasma homocystein levels in diffuse SSc, was significantly higher than limited SSc (F = 19.22 p < 0.001). Conclusion: Numerous clinical studies have been published on the association between homocysteine and vascular diseases. It has been shown to be cytotoxic to endothelium, to induce a vascular-endothelial cell activator, and to promote smooth muscle cell proliferation. Our finding of Significantly higher plasma homocysteine levels in the both subgroups of SSc implicate the contribution of hyperhomocysteinemia to endothelial damage in this disease.